2013
DOI: 10.1590/s0100-736x2013000700005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology and extended-spectrum β-lactamases production of Klebsiella pneumoniae isolated from three dairy herds

Abstract: Pesq. Vet. Bras. 33 (7) The objectives of this study were to isolate Klebsiella pneumoniae from different sources in three dairy cattle herds, to use the pulsed-field gel electrophoresis (PFGE) to measure genotypic similarities between isolates within a dairy herd, to verify the production of extended-spectrum β-lactamases (ESBLs) by the double-disk synergy test (DDST), and to use the PCR to detect the main ESBLs subgroups genes. Three dairy farms were selected based on previous mastitis outbreaks caused by K.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…The frequency of ESBL-producing Enterobacteriaceae reported in this study (3.3%) agrees with other studies conducted in bulk-tank milk samples in Switzerland, Brazil, India, the Czech Republic, Indonesia, and Germany, which reported prevalences ranging between 0 and 9% (Geser et al, 2012;Nóbrega et al, 2013;Rasheed et al, 2014;Skočková et al, 2015;Sudarwanto et al, 2015;Odenthal et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…The frequency of ESBL-producing Enterobacteriaceae reported in this study (3.3%) agrees with other studies conducted in bulk-tank milk samples in Switzerland, Brazil, India, the Czech Republic, Indonesia, and Germany, which reported prevalences ranging between 0 and 9% (Geser et al, 2012;Nóbrega et al, 2013;Rasheed et al, 2014;Skočková et al, 2015;Sudarwanto et al, 2015;Odenthal et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover there was great difference Science Publications AJID between the prevalence of Klebsiella isolated from various apparently healthy animal origins, as it was higher in sheep, followed by cow, goats and lastly camels with percentages of 8.5, 5.5, 4.1 and 3.9%, respectively (Table 3). These findings support the statement by Diego et al (2013) who reported that, the natural flora of the intestine includes a large population of coliform bacteria including Klebsiella pneumoniae. Faeces are an important source of these organisms in the environment.…”
Section: Discussionsupporting
confidence: 92%
“…The most common response of the cell to antibiotics is to cease growing (bacteriostasis), but classes of compounds such as β-lactams, continued growth is permitted, with inhibition of the target in the organism leading indirectly to cell death. There has been growing concern about antimicrobial resistance for some years now (Diego et al, 2013). The antibiogram of pathogens could be variable from place to place and from case to another.…”
Section: Discussionmentioning
confidence: 99%
“…The 67.4% Klebsiella isolation prevalence suggested that the genus may have the capacity of acquiring genes encoding for ESBLs more than Salmonella and E. coli with isolation prevalence of 23.9% and 8.7%, respectively. Among ESBL-resistant enterobacteria, Klebsiella acquired the greatest variety of genes encoding for ESBLs production and it produced the greatest variety of ESBLs (Paterson et al, 2003;Nobrega et al, 2013). Studies conducted elsewhere in Africa also reported isolation of ESBL-resistant Klebsiella more frequently than any other genus in Enterobacteriaceae (Blomberg et al, 2005;Gangoue-Pieboji et al, 2005).…”
Section: Discussionmentioning
confidence: 99%